A crítica hegeliana do entendimento e a perspectiva da razão - Bezerra, Hildemar de Araújo (2011)
The aim of this work is to present the critic of Hegel to the form of thinking of the Understanding (Verstand) and the perspective of a new concept of Reason (Vernunft) or rationality that then appears, and this tends as base the three moments of the logical process (the moment of the Understanding, Dialectical and the Speculative) presented by Hegel in the Encyclopedia of the Philosophical Sciences. It will be shown that this critic is done immanent to the own philosophy of Hegel, because the Understanding is so much the object of the critic, as one of the moments that constitute the own process logical-dialectic (method dialectic) that defines the rationality hegelian. Starting from that insert of the Understanding in the own Reason, we will see that the critic of Hegel won't just feel in a destructive way, in a such way that the Understanding totally goes denied, but before it will elevate this same Understanding at the level of the Reason speculative, removing like this your assumed place of absolute university of the truth and pointing it in your true place.